Microenvironment heterogeneity affected by anthropogenic wildfire-perturbed soil mediates bacterial community in Pinus tabulaeformis forests - Liu, Guanhong; Gu, Ze; Liu, Xiaodong; Li, Bingyi (Frontiers in Microbiology, 2024)
In recent years, the frequency and intensity of anthropogenic wildfires have drastically increased, significantly altering terrestrial ecosystems. These fires impact soil environments and microbial communities, affecting ecosystem structure and function. This study investigated the impact of wildfire intensity and soil stratification on soil physicochemical properties and microbial diversity within Pinus tabulaeformis forests in North China. Soil samples were collected from different fire severity zones (Control, Light, Moderate, High) and depths (topsoil: 0-10 cm; subsoil: 10-20 cm). Analyses included measurements of soil pH, organic carbon (SOC), total nitrogen (TN), and other nutrients. Microbial diversity was assessed using 16S rRNA gene sequencing. Our findings revealed significant variations in soil pH, SOC, TN, and other nutrients with fire severity and soil depth, profoundly affecting microbial community composition and diversity. Soil pH emerged as a critical determinant, closely linked to microbial α-diversity and community structure. Fire severity significantly altered soil pH (p = 0.001), with topsoil microbial communities differentiating between burned and unburned conditions, while subsoil layers showed more pronounced effects. Proteobacteria consistently dominated across all conditions, while Acidobacteriota and Actinobacteriota increased in high-severity and light/moderate-severity areas, respectively. Verrucomicrobiota were more prevalent in control samples, and Chloroflexi and Bacteroidota increased in moderate and high-severity areas. Correlation analyses illustrated significant relationships between soil environmental factors and dominant bacterial phyla. This study highlights the significant long-term effects of wildfires on soil heterogeneity and bacterial communities in Pinus tabulaeformis forests. Fire severity significantly influences soil pH, affecting nutrient dynamics and enhancing microbial diversity. The results underscore the importance of soil stratification, with different soil layers showing varying responses to fire severity, highlighting the need for tailored management strategies. Future research should focus on long-term monitoring of microbial recovery and nutrient cycling post-wildfire. Investigating specific microbial taxa's roles in ecosystem resilience and exploring soil amendments to optimize pH and nutrient availability could enhance post-fire recovery, supporting sustainable ecosystem recovery and resilience.